2013
DOI: 10.3390/ijms140611795
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Production and Behavior of Hydroperoxyacids in Heterotrophic Bacteria Attached to Senescent Phytoplanktonic Cells

Abstract: The photooxidation of cellular monounsaturated fatty acids was investigated in senescent phytoplanktonic cells (Emiliania huxleyi) and in their attached bacteria under laboratory controlled conditions. Our results indicated that UV-visible irradiation of phytodetritus induced the photooxidation of oleic (produced by phytoplankton and bacteria) and cis-vaccenic (specifically produced by bacteria) acids. These experiments confirmed the involvement of a substantial singlet oxygen transfer from senescent phytoplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…3.1. Singlet oxygen transfer efficiency Petit et al (2013) previously showed that the photodegradation state of attached bacteria was well correlated with the degradation of chlorophyll a in phytodetritus. If chlorophyll a constitutes the main inducer of type II photosensitized oxidation in phytodetritus (Nelson, 1993), CDOM, which is produced increasingly during irradiation (Coelho et al, 2011;Cory et al, 2008Cory et al, , 2010Dalrymple et al, 2010) can induce the production of singlet oxygen in the aqueous phase (Sandvik et al, 2000) and thus impact bacteria (Glaeser et al, 2010).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…3.1. Singlet oxygen transfer efficiency Petit et al (2013) previously showed that the photodegradation state of attached bacteria was well correlated with the degradation of chlorophyll a in phytodetritus. If chlorophyll a constitutes the main inducer of type II photosensitized oxidation in phytodetritus (Nelson, 1993), CDOM, which is produced increasingly during irradiation (Coelho et al, 2011;Cory et al, 2008Cory et al, , 2010Dalrymple et al, 2010) can induce the production of singlet oxygen in the aqueous phase (Sandvik et al, 2000) and thus impact bacteria (Glaeser et al, 2010).…”
Section: Resultsmentioning
confidence: 92%
“…coccoliths) could reduce the lifetime of 1 O 2 and inhibit its migration to bacterial biomass. Indeed, if the transfer of 1 O 2 is strongly favoured between two lipophilic membranes (such as those of phytoplankton and associated bacteria; Petit et al, 2013), this excited form of oxygen might be quickly deactivated if the two membranes are separated by a polar structure. Thus charged mineral surfaces, such as frustules or coccoliths, may allow for enhanced bacterial growth and biodegradation of phytodetritus by inhibition of 1 O 2 transfer.…”
Section: Introductionmentioning
confidence: 99%
“…1 O 2 is more stable in hydrophobic environments such as membranes (Ogilby, ), and this can facilitate the transfer from one cell to the other if they attach via membranes, for instance. Consistently, senescent (matrix‐less) green algae, as well as coccolithophores, which can shed their coccolith plates during senescence, both transfer 1 O 2 to attached bacteria (Petit et al ., ). Additionally, transfer of 1 O 2 from senescent diatoms is inversely related to silica concentration, and thus extent of frustule formation (Petit et al ., ).…”
Section: Biological Sources Of Extracellular Rosmentioning
confidence: 97%
“…This toxic effect has implications for both free and sinking‐particle associated phytoplankton cells and their associated heterotrophic colonizers. 1 O 2 damages the heterotrophs via oxidation of their lipids ( cis ‐vaccenic acids) (Rontani et al ., ; Petit et al ., ). An open question remains if this results in a strongly asymmetric cellular stress at the point of cell–cell contact, or if 1 O 2 can diffuse within the hydrophobic interior of the cytoplasmic membrane and impact larger regions of the cell envelope.…”
Section: Biological Sources Of Extracellular Rosmentioning
confidence: 97%
“…While results did not show any specific FA marker of the frustule, 456 frustule-associated FA were characterised by a very low degree of unsaturation with 457 predominance of14:0, 16:0 and 18:0 FA. Although high pH (NaOH 1 mol.l -1 ) and the absence 458 of chlorophyll favour neither autoxidation nor photooxidation (Petit et al, 2013;Rontani, 459 2001), the reactivity of unsaturated FA to oxidation could have led to a decrease of 460 unsaturation degree due to experimental conditions and extraction process. However, tests to 461 determine the effect of temperature (70 °C) on polyunsaturated FA (20:4(n-6)), and previous 462 observations that report unsaturated FA conservation during hot saponification (> 100 °C, see 463 section 2.7.1), suggest that our protocol had little effect on FA unsaturation.…”
Section: Discussionmentioning
confidence: 99%